Clinical and experimental application of the percutaneous twitch superimposition technique for the study of human muscle activation. Issue 11 (November 1986) - Rutherford, O M; Jones, D A; Newham, D J
Abstract : The use of percutaneous stimulation for twitch superimposition in the human quadriceps has been compared with stimulation via the femoral nerve. It was found that the relationship between the extra force generated by the twitch and the level of voluntary contraction was independent of the percentage of the muscle stimulated. The technique was used to study activation of the quadriceps and biceps in a group of young healthy adults, and quadriceps activation in patients with musculo-skeletal disorders. The majority of subjects could fully activate their muscles during brief isometric contractions. Inhibition was demonstrated in patients with muscle pain and joint pathology and in subjects with a previous history of knee or joint injury. The technique is easy to use and provides a simple way of detecting inhibition where it might not be anticipated, such as in the absence of pain. Where inhibition is demonstrated the technique can be used to predict approximately the maximum force available.